2023
DOI: 10.1088/1367-2630/ace471
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the fundamental bending vibration of a linear polyatomic molecule for symmetry violation searches

Abstract: Polyatomic molecules have been identified as sensitive probes of charge-parity violating and parity violating physics beyond the Standard Model (BSM). For example, many linear triatomic molecules are both laser-coolable and have parity doublets in the ground electronic X 2Σ+(010) state arising from the bending vibration, both features that can greatly aid BSM searches. Understanding the X 2Σ+(010) state is a crucial prerequisite to precision measurements with linear polyatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Following this roadmap with heavier trapped polyatomic molecules has the potential to provide orders-of-magnitude improvements to present bounds on T-violating physics. Using a recent study of the X˜010 state in YbOH ( 37 ), we identified similar N = 1 zero g -factor states for eEDM measurements with greatly improved sensitivity. In addition to the g -factor tuning demonstrated in this work, polyatomic molecules provide the ability to reverse the sign of Σ without reversing M S , which is a crucial feature of recent experiments that has greatly improved the limit on the eEDM ( 25 , 27 ).…”
Section: Discussion and Outlookmentioning
confidence: 88%
“…Following this roadmap with heavier trapped polyatomic molecules has the potential to provide orders-of-magnitude improvements to present bounds on T-violating physics. Using a recent study of the X˜010 state in YbOH ( 37 ), we identified similar N = 1 zero g -factor states for eEDM measurements with greatly improved sensitivity. In addition to the g -factor tuning demonstrated in this work, polyatomic molecules provide the ability to reverse the sign of Σ without reversing M S , which is a crucial feature of recent experiments that has greatly improved the limit on the eEDM ( 25 , 27 ).…”
Section: Discussion and Outlookmentioning
confidence: 88%